2019
DOI: 10.1111/jdv.15985
|View full text |Cite
|
Sign up to set email alerts
|

Triggering factors in sensitive skin from the worldwide patients’ point of view: a systematic literature review and meta‐analysis

Abstract: Sensitive skin (SS) is a syndrome defined by the occurrence of unpleasant sensations in response to stimuli that normally should not provoke such sensations. In most patients, symptoms occur within 1 h following exposure to trigger factors and may persist for minutes or even hours. Numerous triggering factors (physical, chemical or psychological) are suspected and described in articles. The aim of this article was to perform a systematic literature review to collect data on the triggering factors involved in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 26 publications
5
45
0
Order By: Relevance
“…40 Thirteen studies were included representing 20 486 subjects. A recent literature review with a meta-analysis analysed the role of environmental factors on sensitive skin.…”
Section: Role Of Environmental Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…40 Thirteen studies were included representing 20 486 subjects. A recent literature review with a meta-analysis analysed the role of environmental factors on sensitive skin.…”
Section: Role Of Environmental Factorsmentioning
confidence: 99%
“…40 The presence of potentially irritating substances in their composition (alpha-hydroxy acids, propylene glycol, alcohol fragrances, preservatives, surfactants and others) increases the possibility of the occurrence of symptoms. Since only exposure study showed a role of hair dyes on sensitive scalp and facial sensitive skin, 41,65 hair dyes should be avoided, in particular those containing ammonia.…”
Section: Avoidance Of Triggersmentioning
confidence: 99%
See 3 more Smart Citations